1991
DOI: 10.1089/hyb.1991.10.347
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genetically Engineered Immunoconjugates of Lymphotoxin and a Chimeric Anti-Ganglioside GD2 Antibody

Abstract: Human lymphotoxin was genetically conjugated to the constant region of a human gamma 1 immunoglobulin gene at the end of either the second (CH2-LT) or third (CH3-LT) constant region domain. The altered heavy chain constant regions were combined in a plasmid vector together with the variable regions of a mouse anti-ganglioside GD2 antibody 14.18 and the human kappa constant region. The resulting immunoconjugate constructs were expressed in transfected hybridoma cells and tested for both their antibody and lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…The effector functions of the CH3-IL2 protein-i.e., the ability to mediate complement and Fc receptor-dependent lysis-were also tested and found to be maintained (but somewhat decreased) when compared with that of the chimeric 14.18 antibody (data not shown). A similar result was reported for the CH3-lymphotoxin fusion protein (15 Fig. 4A.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The effector functions of the CH3-IL2 protein-i.e., the ability to mediate complement and Fc receptor-dependent lysis-were also tested and found to be maintained (but somewhat decreased) when compared with that of the chimeric 14.18 antibody (data not shown). A similar result was reported for the CH3-lymphotoxin fusion protein (15 Fig. 4A.…”
supporting
confidence: 89%
“…Thus, fusion of this cytokine at the carboxyl terminus of an antibody or antibody fragment does not significantly reduce its activity. We reported a similar result when we found that lymphotoxin (tumor necrosis factor /) retained its full activity when fused to the end of the CH3 domain (15). However, in that case some inactivation of lymphotoxin activity occurred during the elution from the protein A-Sepharose column.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Mouse-human chimeric antibodies directed against the EGF receptor (ch225) or GD2 (chl4.18) were constructed by joining the cDNA for the variable region of the murine antibodies with the constant regions of the yl heavy chain and the K light chain as described (19 proteins ch225-IL2 and chl4.18-IL2 were constructed by fusion of a synthetic sequence coding for human IL-2 to the carboxyl end of the human Cyl gene as described (12,14,20 tAll experimental groups were started with six mice for the hepatic and eight mice for the lung metastases models; animals found dead prior to the planned date of sacrifice were not included in the evaluation. §Differences in the metastatic score/number of metastatic foci and organ weights between the fusion protein groups and all control groups were statistically significant (P < 0.002).…”
mentioning
confidence: 99%
“…The application of recombinant DNA technology has recently led to the construction of antibody-cytokine fusion proteins designed to achieve optimal biological effectiveness by combining the unique targeting ability of antibodies with the multifunctional activities of cytokines (14,19,20). Antibody-cytokine fusion proteins have been proposed for the treatment of solid tumors, including melanoma (14) and Table 1.…”
Section: Discussionmentioning
confidence: 99%